Pengaruh Penggunaan Lembar Kerja Berbasis Inkuiri Kontekstual terhadap Kemampuan Berfikir Tingkat Tinggi Mahasiswa dalam Pembelajaran Biologi Air - Kusumawati, Diah; Nasution, Unita Sukma Zuliani; Haryati, Haryati (Journal of Natural Sciences, 2023)
This research aims to investigate the impact of using contextual inquiry-based worksheets on the higher-order thinking skills of students in aquatic microbiology. The study employed a quasi-experimental design with pretest-posttest measures. The research population comprised six classes, and samples were drawn from three classes determined through random sampling, namely Regular Class (A) with 40 students (application of contextual inquiry-based worksheets), Extension Class (A) with 25 students (application of Problem-Based Multimedia Pedagogy - PBMP worksheets), and Extension Class (B) with 22 students (application of conventional worksheets). Data analysis was conducted using the Anacova method with SPSS 23.00 for Windows. Data were collected through descriptive test instruments in the form of essays and questionnaires. The results of the data analysis indicated that contextual inquiry-based worksheets yielded better outcomes compared to both contextual PBMP and conventional worksheets. The mean score for higher-order thinking skills was 86.93, with a significance level of 0.034, which is less than 0.005.